Fatty acid composition of the bovine milk fat globules obtained by gravity separation - M., Martini (2023)
Gravity separation of milk fat is the process by which fat globules tend to gather on the surface and form a layer of cream. The aim of this study was to assess the differences in the lipid quality of cow milk fractions after gravity separation. Bulk cow milk samples were taken from an individual farm and subjected to gravity separation for 24 h at 4°C. Three fractions were separated. The diameter (μm), the number of fat globules per ml and fatty acid profile of each fraction were determined. The top fraction showed a significantly higher average diameter and number of globules/ml than the middle and lower fractions. In addition, the bottom fraction showed higher amounts of oleic acid, linolenic acid, arachidonic acid and CLA. The interest in gravity separation is due both to its technological applications the possibility of obtaining dairy products with different physical characteristics also in terms of fat nutritional value.